A comparative study on photosynthetic characteristics and flavonoid metabolism between Camellia petelotii (Merr.) Sealy and Camellia impressinervis Chang &Liang - Huang, Xin; Qin, Bo; Qin, Lei; Peng, Zhihong; Xia, Shitou; Su, Yi; Sun, Kaidao; Peng, Keqin (Frontiers in Plant Science, 2022)
Camellia petelotii (Merr.) Sealy and Camellia impressinervis Chang & Liang belong to the golden subgroup of Camellia (Theaceae). This subgroup contains the yellow-flowering species of the genus, which have high medicinal and ornamental value and a narrow geographical distribution. These species differ in their tolerance to high light intensity. This study aimed to explore the differences in their light-stress responses and light damage repair processes, and the effect of these networks on secondary metabolite synthesis. Two-year-old plants of both species grown at 300 µmol·m-2·s-1 photosynthetically active radiation (PAR) were shifted to 700 µmol·m-2·s-1 PAR for 5 days shifting back to 300 µmol·m-2·s-1 PAR for recovery for 5 days. Leaf samples were collected at the start of the experiment and 2 days after each shift. Data analysis included measuring photosynthetic indicators, differential transcriptome expression, and quantifying plant hormones, pigments, and flavonoids. Camellia impressinervis showed a weak ability to recover from photodamage that occurred at 700 µmol·m-2·s-1 compared with C. petelotii. Photodamage led to decreased photosynthesis, as shown by repressed transcript abundance for photosystem II genes psbA, B, C, O, and Q, photosystem I genes psaB, D, E, H, and N, electron transfer genes petE and F, and ATP synthesis genes ATPF1A and ATPF1B. High-light stress caused more severe damage to C. impressinervis, which showed a stronger response to reactive oxygen species than C. petelotii. In addition, high-light stress promoted the growth and development of high zeatin signalling and increased transcript abundance of adenylate dimethylallyl transferase (IPT) and histidine-containing phosphotransferase (AHP). The identification of transcriptional differences in the regulatory networks that respond to high-light stress and activate recovery of light damage in these two rare species adds to the resources available to conserve them and improve their value through molecular breeding.